ВПЛИВ З’ЄДНУВАЛЬНОГО ВИСОКОВОЛЬТНОГО КАБЕЛЮ НА СТРУМИ І НАПРУГИ У ПРИСТРОЇ ІМПУЛЬСНОГО БАР’ЄРНОГО РОЗРЯДУ - Берека, В.О.; Васецький, Ю.М.; Кондратенко, І.П. (Інститут електродинаміки НАН України, Київ, 2024)
The article is devoted to the study of the connecting cable influence, as an element with distributed parameters between the pulsed generator and discharge chamber in the electrical complex based on pulsed barrier discharge, to the values of currents and voltages in the system. Based on experimental studies and modeling, it has been established that the currents at different ends of the cable differ significantly from each other, which is due to the large value capacitive pulsed charging current of the cable. It has been established that during the barrier discharge, a correctly measured pulse current has significantly shorter duration than pulse of voltage. During the electrical discharge, a feature of the dependence of the current at the input to the cable is the appearance of an additional local maximum, of much smaller amplitude with a time shift equal to the time the electromagnetic wave movement along the cable. It has been shown that the use of the connecting cable of increased length makes it possible to increase the voltage between the electrodes of two times in comparison with the voltage at the cable input, without taking into account the voltage drop across the internal resistance of the generator when the cable length no less than twice the path length that the electromagnetic wave moves during the time from start of the pulse to maximum value generator pulse. References 16, figures 7.